Structural and community change outcomes of the Connect-to-Protect Coalitions: Trials and triumphs securing adolescent access to HIV prevention, testing, and medical care - Miller, Robin Lin (Am J Community Psychol, 2017)
Connect to Protect (C2P), a 10-year community mobilization effort, pursued the dual aims of creating communities competent to address youth’s HIV-related risks and removing structural barriers to youth health. We used Community Coalition Action Theory (CCAT) to examine the perceived contributions and accomplishments of 14 C2P coalitions. We interviewed 318 key informants, including youth and community leaders, to identify the features of coalitions’ context and operation that facilitated and undermined their ability to achieve structural change and build communities’ capability to manage their local adolescent HIV epidemic effectively. We coded the interviews using an a priori coding scheme informed by CCAT and scholarship on AIDS-competent communities. We found community mobilization efforts like C2P can contribute to addressing the structural factors that promote HIV-risk among youth and to community development. We describe how coalition leadership, collaborative synergy, capacity building, and local community context influences coalitions’ ability to successfully implement HIV-related structural change, demonstrating empirical support for many of CCAT’s propositions. We discuss implications for how community-mobilization efforts might succeed in laying the foundation for an AIDS-competent community.